Foreign Policy as Domestic Power Struggle: The Northern Iraq as a Battlefield Between the AKP and the TAF in 2007-8 - Ali Balcı (Türkiye Ortadoğu Çalışmaları Dergisi, 2015)
The issue of rapprochement with Kurdish parties in the Northern Iraq turned a discursive battlefield between Turkish Armed Forces (TAF) and the ruling Justice Development Party (AKP) after the 2005 General Elections in Iraq from which Kurdish groups emerged as a strong political actor in Iraqi politics. When the AKP government declared its policy of rapprochement with the Kurdish regional government at the beginning of 2007, the then Chief of General Staff Yaşar Büyükanıt publicly criticized and rejected this new policy. Büyükanıt declined to talk with Kurdish leaders on the grounds that they were supporting for the PKK. This exchange of statements was the part of a political snowball rolling to which other areas of the struggle were included. The rift between the AKP government and the TAF over how to deal with Iraqi Kurds started just as Turkey gears up for key presidential elections. This paper will attempt to analyze the battle over the Northern Iraq between the TAF and the AKP in order to answer the following questions: How the TAF and the AKP came face to face on the issue of the Northern Iraq? Under what conditions the Northern Iraq turned a discursive battlefield between the TAF and the AKP? What was the function of the Northern Iraq in the domestic power struggle between the TAF and the AKP?